2017
DOI: 10.1103/physreva.95.063819
|View full text |Cite
|
Sign up to set email alerts
|

Formalism of optical coherence and polarization based on material media states

Abstract: The fluctuations or disordered motion of the electromagnetic fields are described by statistical properties rather than instantaneous values. This statistical description of the optical fields is underlying in the Stokes-Mueller formalism that applies to measurable intensities. However, the fundamental concept of optical coherence, that is assessed by the ability of waves to interfere, is not treatable by this formalism because it omits the global phase. In this work we show that, using an analogy between dete… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 24 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…To handle such processes, one must start with the coherent Jones formalism and then switch to the Mueller one. The formalism based on 4×4 Z states that we developed recently [29,30] is particularly suitable for this kind of evaluation since it allows for a direct calculation. If we consider the system setup of Fig.…”
Section: A Appendix: Calculation Of the Detected Intensitymentioning
confidence: 99%
“…To handle such processes, one must start with the coherent Jones formalism and then switch to the Mueller one. The formalism based on 4×4 Z states that we developed recently [29,30] is particularly suitable for this kind of evaluation since it allows for a direct calculation. If we consider the system setup of Fig.…”
Section: A Appendix: Calculation Of the Detected Intensitymentioning
confidence: 99%
“…As it was discussed in Refs. [19,20] the outer product |h h| generates a 4 × 4 covariance scattering matrix of rank 1 that can be considered as an analog of a pure state in quantum mechanics. In terms of covariance vectors we can, alternatively, write the decomposition in Eq.…”
Section: Decomposition Of the Scattering Matrix Of The Coupled Dmentioning
confidence: 99%
“…(26) and (27) are symmetric, the fourth component of these covariance vectors is always zero. This reads as an absence of circular polarization effects [19,21].…”
Section: Decomposition Of the Scattering Matrix Of The Coupled Dmentioning
confidence: 99%
“…In previous works [1], [2] there were two different representations of Mueller-Jones states: the covariance vector |h and the Z matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The same depolarization scheme given in [2] applies to this quaternion formulation as well. But, in the following it will be shown that there exists a Mueller quaternion with matrix coefficients which can transform the Stokes quaternion for depolarizing and nondepolarizing processes.…”
Section: Introductionmentioning
confidence: 99%